Bosutinib in the real‐life treatment of chronic myeloid leukemia patients aged >65 years resistant/intolerant to previous tyrosine‐kinase inhibitors. Issue 3 (13th March 2021) - Latagliata, Roberto; Attolico, Immacolata; Trawinska, Malgorzata Monika; Capodanno, Isabella; Annunziata, Mario; Elena, Chiara; Luciano, Luigiana; Crugnola, Monica; Bergamaschi, Micaela; Bonifacio, Massimiliano; Baratè, Claudia; Mauro, Endri; et al.
Abstract: To evaluate the role of bosutinib in elderly patients aged >65 years with chronic myeloid leukemia (CML), a real‐life cohort of 101 chronic‐phase CML patients followed up in 23 Italian centers and treated with bosutinib in second or a subsequent line was retrospectively evaluated. Starting dose of bosutinib was 500 mg/day in 25 patients (24.8%), 400 mg/day in 7 patients (6.9%), 300 mg/day in 33 patients (32.7%), 200 mg/day in 34 patients (33.6%), and 100 mg/day in 2 patients (2.0%). Grade 3/4 hematological toxicity occurred in 7/101 patients (6.9%) and grade 3/4 extra‐hematological toxicity in 19/101 patients (18.8%). Permanent bosutinib discontinuation due to toxicity was needed in 12 patients (11.9%). Among the 96 patients evaluable for response, 74 (77.0%) achieved a complete cytogenetic response (CCyR), while 64 of these 74 patients in CCyR (66.6% of all 96 evaluable patients) also achieved a molecular response (MR) (major MR [MR 3.0] in 21 [21.8%], deep MR [MR 4.0/4.5] in 43 [44.8%]). The 3‐year event‐free survival and overall survival of the whole patients' cohort from bosutinib start were 60.9% (CI 95% 49.3–72.5) and 86.4% (CI 95% 77.2–95.6), respectively. Our real‐life data show that bosutinib is effective, with a favorable safety profile, also in elderly patients with important comorbidities and resistance and/or intolerance to previous tyrosine‐kinase inhibitor treatments. As a consequence, it could play a significant role in current clinical practice for frail patients.